Refórmese el numeral 2 del artículo 4, del título v del libro segundo del código de la niñez y adolescencia, con respecto a la edad en que el hijo o hija debe recibir alimentos - Romero Román, Flor Verónica (2017)
Article 4 paragraph 2 of Title V of Book II of the Code of Children and Adolescents states: "They are entitled to claim maintenance: 2. adults or adults up to the age of 21 years to show that they are studying at any level education to prevent them or hinders engage in productive activity and lack of friends and sufficient resources ...... ", as it is almost impossible for an adult ends up when he enrolled in the 21-year-old career is known, because if we account usually a person finishes his studies of school at age 18, and the races that exist in our country are usually 5 years of study. In addition to this articulated, it would be limiting to many adults under 21 years of age, can not study and finish his career; and thus not be able to become professionals with a college degree, therefore it would infringe the right to education that we each people. As noted, is necessary for legal reform to this article, so that in this way the parent to continue through alimony until your child has the age of 24 years, because if we remember that he finished his studies of school at 18 years of age, and race you have chosen has a duration of 5 years, he at the age of 24 years and could have obtained a university degree.